MESSAGE FROM THE EDITOR-IN-CHIEF - Datuk Prof. Dr. Hjh. Bibi Florina Abdullah, (The Malaysian Journal of Nursing (MJN), 2009)
As with professions and skilled services across the board in today's times, nursing has had to keep running just to keep up! And I must say we have done that commendabl y. These days, the best nurse prospects who are drawn to the profession talk about degrees and, indeed, even PhDs.These are women who are compassionate yet competitive, gifted yet tireless, and they do the profession proud. To be sure, this calibre of nurses are their own bosses, in a way. They are able to assess cases, make their own diagnoses, and discuss the history of case management and the role of case manager.This is because they are trained specialist nurses who have been equipped with the skills to support doctors and specialists in the treatment and management of cases like never before. This speaks very well for both the quality and quantity of nurse training - both in Malaysia and worldwide. On our shores today. the level of teaching and training proferred by the numerous nursing colleges and institutes has the capability to produce, for instance, cardiac nurses who are competent and confident from the word 'go'. Hence, it speaks to the profession that as the need for qualified nursing personnel grows, so does the need for continuing nursing education.The more knowledgeable and experienced a nurse is, the more units and patients she can help. Not only that, by sharpening current skills and learning new ones, nurses even create opportunities for themselves in travel nursing, and other employment ventures. So, exciting and challenging times lie ahead for the profession. As this journal was conceived primarily to facilitate communication and help nurture the industry's tomorrows today, we earnestly seek your support and input. Please get in touch with us with your ideas, questions and issues and together we can grow!